The Dynamics of an Oscillating Enzymatic Reaction Network is Crucially Determined by Side Reactions. Issue 1 (11th November 2020) - Pogodaev, Aleksandr A.; Lap, Tijs T.; Huck, Wilhelm T. S.
Abstract: Synthetic complex chemical systems are often subject to perturbations in reaction conditions. To ensure robust functioning of these systems in real‐world applications, a better understanding is required of how resilience to perturbations could be included in the design of these systems. In order to develop such an understanding we need a deeper insight into how chemical systems respond to perturbations. Here, we study the effect of spiking concentrations in an oscillating enzymatic reaction network. We identify that a different magnitude of a perturbation triggers two distinctive responses: obtaining sustained oscillations and causing the loss of the amplitude. We rationalise our findings based on non‐linear dynamics and identify that non‐essential side reactions crucially tailor the observed behaviour. Abstract : The dose makes the poison : Complex chemical systems are often subject to perturbations and fluctuations in conditions. For real world applications of such systems we need to learn how to design robust and resilient systems. Using an oscillating reaction network as an example, we found that a perturbation at the same position, but with different magnitude can help the system to achieve sustained oscillations or induce the collapse of the system.